Career self-efficacy among undergraduate student in a public university - Mohd Izwan Mahmud,; Chang, Peng Kee; Zalinda Othman,; Salleh Amat, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Career readiness among university students including careerplanning, choosing and making career decisions. This study aims to identify the career self-efficacy among first-degree students and to measure the differences between education field clusters and gender. This study uses survey design to identify the student’s career self-efficacy pattern. 1391 first-degree students involved as sample in this study. Instrument used in this study is Career Decision Self-Efficacy (CDSE-SF). Data was analysed descriptively, t-test and one-way ANOVA. Results found that career self-efficacy level was low (1.5%), moderate (37.1%) and high (61.4%). One-way ANOVA analysis shows that there are no significant differences between science and technology, health and medical science, and social science [F (2.1388) = 2.81, p > .05]. While t-test found that there are no significant differences between gender [t = -1.539, p > .05]. This study implies that first-degree students that have low and moderate level career readiness needs appropriate intervention. Implication of this study to develop career profiling and build a career intervention programs based on needs of the students. Also the important of career counsellor in university to enhance graduate employability rate through a systematic career development programs. Future study needs to focus on the career intervention that improves career readiness among students. And also focus on longitudinal study to comparison of the few batches of the undergraduate students.